Importance of cultivated long-lived species and the challenges for their propagation - Chura Llanos, Luz Satomi (2023)
In this article, a bibliographic review was carried out on the economic, touristic and environmental importance of long-lived species and the problems related to their vegetative propagation for their conservation. Many of these species grow in the inter-Andean valleys of Peru and have adapted over the time to adverse locations compared to those in which they usually grow. This has allowed them to develop unique phenotypes that store valuable genetic information and should be conserved. However, these present species problems of vegetative propagation, a problem explained throughout this article. We conclude that, despite the great importance of these species, their age factor is the main problem for their propagation, their conservation and diversity.